ASUPAN VITAMIN D DAN TINGKAT KEPARAHAN DEMAM BERDARAH DENGUE PADA ANAK USIA 1-14 TAHUN DI YOGYAKARTA - , Nur Siyam, Prof. dr. Siswanto Agus Wilopo, SU, M.Sc, Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: DHF can lead to shock and death. In early 2012, 62,44% of DHF in Yogyakarta on child age 1-12 years, the majority have DHF severity. Lower of vitamin D intake assumed cause of DHF severity. This assumption need to be proved. Objective: To analyse the effect of the vitamin D intake and DHF severity in children 1- 14 year. Methods: This study is an observational analytic with hospital-based case control study design. The research conducted in inpatient wards children and medical record installation in Jogja Hospital and RSUP Dr. Sardjito on year of 2013. The case group was children 1-14 years who were diagnosed with DHF grade III & IV, the control group was DHF grade I & II based on medical diagnosis and laboratorium checking. Sampling technique with consecutive sampling. Data intake of vitamin D was obtained by FFQ. External variables were age, IMT, status of chronic disease, and tensity of morning sun exposure. Determination of the cut-off point value of sensitifity and spesifisity DHF severity based on vitamin D intake and IMT with ROC curve. Data analysis with univariable, bivariable (t-test), and multivariable (logistic regretion). Results: The number of subject was 120 (60 cases and 60 controls) without matching. Vitamin D intake cut-off point based on ROC Curve was 2,7 Î¼g/day. The results of the t test showed severe DHF patients had mean of vitamin D intake of 1.10 times less than in non-severe dengue. Logistic regresi test showed that vitamin D intake <2,7 Î¼g/day, BMI 18,75 kg/m2, chronic disease and intensity of morning sun exposure <15 min/day were increased risk of DHF severity (OR=0,47